IMPLEMENTASI CONTINUOUS IMPROVEMENT DALAM PENINGKATAN MUTU PENDIDIKAN ISLAM DI PKBM IBNU TAIMIYAH BUKITTINGGI - Fahril Syahweli; Zulfani Sesmiarni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Quality improvement has become a fundamental necessity for Islamic educational institutions in responding to modernization, digital transformation, and societal demands for high-quality education services. PKBM Ibnu Taimiyah Bukittinggi, as a non-formal Islamic educational institution, is required to implement a sustainable quality improvement system to remain relevant and adaptive. This study aims to analyze the implementation of continuous improvement in Islamic education at PKBM Ibnu Taimiyah Bukittinggi through the application of the Plan-Do-Check-Act (PDCA) cycle, Kaizen culture, educational innovation, teacher professional development, and the documentation of lesson learned and best practice. The research employed a qualitative descriptive approach using literature review, field observation, and institutional document analysis. The findings indicate that continuous improvement has been implemented through regular evaluation of learning programs, strengthening memorization monitoring systems, improving teacher competencies, and digital-based learning innovation. The implementation of PDCA assists the institution in planning, implementing, evaluating, and improving educational programs systematically. Furthermore, Kaizen culture encourages consistent small improvements by all institutional members. Therefore, the implementation of continuous improvement significantly contributes to enhancing effective, adaptive, and sustainable Islamic education quality at PKBM Ibnu Taimiyah Bukittinggi.